A Developmental Study of Intelligent Retrieval - Keniston, Allen H.; Flavell, John H. (Child development, 1979)
Subjects of grades 1, 3, 7, and college were given incidental memory problem. The experimenter named a letter of the alphabet, the subject wrote it on a small card, the experimenter removed the card and named another letter, and so on until 20 letters had been written. Intelligent retrieval methods for subsequently recalling these letters consisted either of mentally proceeding through the alphabet from the outset and writing down each previously written letter as encountered and recognized, or else first rote recalling some and then switching to the alphabetical strategy. The younger subjects could use the former method skillfully and effectively (i. e., it improved their recall) when merely instructed to do so. There were, however, significant increases with age in the spontaneous use of these methods, in the ability to think of and propose the alphabetical strategy prior to any retrieval experience, and in the apparent ease, completeness, and accuracy with which subjects could report the retrieval methods they had used. It was concluded that the retrieval knowledge, strategies, and skills assessed in this study have important counterparts in everyday, extralaboratory remembering.